ZABURZENIA OSOBOWOŚCI I ICH WPŁYW NA OCENĘ POCZYTALNOŚCI SPRAWCY PRZESTĘPSTWA - Anna Golonka (Zeszyty Prawnicze, 2016)
PERSONALITY DISORDERS AND THEIR EFFECT ON OFFENDERS CRIMINAL RESPONSIBILITY Summary Personality disorders are a relatively common subject of forensic psychiatric opinions. This generally accepted term is usually associated with the concept of psychopathy. However, despite being regarded as a manifestation of a personality disorder, in principle psychopathy precludes the use of Art. 31 § 1 or 2of the Polish Penal Code in court. From the point of view of criminal law it would seem appropriate to distinguish psychopathy from personality disorders, which are sometimes referred to as characteropathy. This distinction is highly relevant in view of its far-reaching consequences as regards the offender’s criminal responsibility. This is confirmed by the results of research on materials relating to specific cases, which warrant a set of conclusions on the effect a personality disorder may have on an offender’s criminal responsibility during the commission of the offence.